Finite element co-simulation and implementation of an eddy current impact seismic source - Jafarzadeh Rastin, Sepideh; Kepic, Anton; Nguyen, H. (2018)
© 2018 SEG. A novel Eddy-current impact seismic source concept has been simulated and bench-tested. This concept seems suitable for lower cost, shallow seismic surveys due to a relatively simple and low-cost mechanical and electrical structure. The creation and interaction between electrical and mechanical components required a computation and simulation approach rather than an analytic approach to assist with understanding and optimizing the concept. Thus, the prototype design was simulated by Finite Element (FEM) analysis using Ansys Maxwell 3D to simulate the electrical-to-mechanical coupling. Much of the simulated performance was verified by measurements from the developed benchtop prototype. Electrical current and inductance measurements were consistent with the simulations; however, some limitations in matching the mechanical design and electrical parameters of the prototype versus the simulation meant that bench prototype didn't match the force values predicted by simulations. Nonetheless, the behavior of the bench-top prototype and confirmation that the simulations generally predict parameters correctly means that the path to a reliable, controllable and economical alternative to small vibrator sources appears feasible.